METHODICAL TRAINING OF FUTURE TEACHERS: IMMERSION IN PROFESSIONAL REALITY - O. V. Tumasheva (Moscow Polytechnic University, 2018)
Modernization of higher education in Russia corresponds to a universal tendency of professionalization of teacher training and strengthening of its practical orientation. At the same time, the theoretical and technological aspects of the practice-oriented methodical training of a future teacher are insufficiently worked out. The author shows that the most perspective approach in this sphere is an immersion in professional reality. This may be achieved by a special form of realization of students' educational activity - professional and pedagogical event (PEE). The paper characterizes the main types of PEE such as research, professional test, subject lessons organized jointly with pupils of secondary schools. The paper introduces a concept of educational and professional task as a form of training material presentation which specifies a research vector. The example of educational and professional task is given. There are also described the stages of the PEE organization: preparatory, forecasting, organization and realization, reflective.